Antioxidant carbon aerogel composite material and preparation method thereof

By introducing borosilicate modified phenolic resin and fibers into the carbon aerogel, the borosilicate modified aerogel composite material is formed and carbonized, the brittleness, low strength and high temperature oxidation problems of carbon aerogel materials are solved, and the material's anti-oxidation and mechanical properties are improved.

CN119797884APending Publication Date: 2025-04-11AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510037363.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the use of carbon aerogel materials, there are problems such as high brittleness, low strength, and easy cracking in large-sized block preparations, and are easily oxidized under high-temperature aerobic environment, which limits its application.

Method used

By introducing borosilicate modified phenolic resin and fibers into carbon aerogels, borosilicate modified phenolic fibers and fiber felts are synthesized by esterification, and borosilicate modified aerogel composite is formed by impregnation and curing, and then carbonization is carried out to achieve synergistic shrinkage and anti-oxidation of the matrix and reinforcement.

Benefits of technology

It significantly improves the oxidation resistance and mechanical properties of carbon aerogel composites, solves the problem of interlayer cracking, and improves the stability and application potential of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235904280000101
    Figure BDA0005235904280000101
  • Figure BDA0005235904280000111
    Figure BDA0005235904280000111
Patent Text Reader

Abstract

The invention discloses an antioxidant carbon aerogel composite material and a preparation method thereof. The method comprises the following steps: synthesizing borosilicate modified phenolic resin; preparing boron-silicon modified phenolic fibers by using the boron-silicon modified phenolic resin; preparing a boron-silicon modified phenolic fiber felt by using the boron-silicon modified phenolic fiber; preparing a boron-silicon modified phenolic aerogel composite material by using the boron-silicon modified phenolic resin and the boron-silicon modified phenolic fiber felt; and carbonizing the boron-silicon modified phenolic aerogel composite material to prepare the boron-silicon modified carbon aerogel composite material. The invention also provides the borosilicate modified phenolic aerogel composite material prepared by the method. According to the invention, heteroatom doping modification is carried out on the reinforcement body and the aerogel matrix through a chemical means, so that the purpose of oxidation resistance of the carbon aerogel body is achieved, and a new way is provided for preparation of the high-temperature-resistant carbon-based thermal insulation material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon aerogel materials, and in particular relates to an oxidation-resistant carbon aerogel composite material and a preparation method thereof. Background Art

[0002] Carbon aerogel is a porous carbon material with high specific surface area, high porosity, low density and good stability. Its excellent temperature resistance makes it have broad application potential in many fields.

[0003] However, in actual use, carbon aerogel materials generally have problems such as high brittleness, low strength, and easy cracking when prepared in large-sized blocks. These problems seriously limit the promotion and application of carbon aerogel materials.

[0004] At present, the most effective way to solve the above-mentioned problems of carbon aerogel materials is to introduce fiber reinforcement into carbon aerogels, thereby improving the toughness and large-size molding stability of carbon aerogel materials.

[0005] However, commonly used fiber reinforcements such as carbon fiber or ceramic fiber hardly shrink during the carbonization process. After being compounded with organic aerogels with a carbonization shrinkage rate of about 25%, there is a problem of shrinkage mismatch during the carbonization process, which causes interlaminar cracking in the composite material and greatly reduces the mechanical strength of the material. Therefore, how to achieve coordinated shrinkage between the reinforcement and the matrix is ​​one of the problems that urgently need to be solved in the field of fiber-reinforced carbon aerogel composites.

[0006] In air, carbon materials begin to oxidize at 450°C, and the oxidation rate increases with the increase of oxidation temperature. The nanoporous structure and high porosity of carbon aerogel will intensify the high-temperature oxidation process of carbon materials in an aerobic environment, which greatly limits the promotion and application of carbon aerogel materials. Therefore, ensuring the stable and long-lasting anti-oxidation of carbon aerogel materials has become a prerequisite for fully utilizing their performance.

[0007] Bulk anti-oxidation is an internal modification technology that modifies the material's own components and passivates the matrix itself, which can essentially solve the problem of oxidation failure of porous carbon materials. Therefore, the development of a method for bulk anti-oxidation of carbon aerogel materials is of great significance for the development and promotion of carbon aerogel composite material technology. Summary of the invention

[0008] In order to solve one or more technical problems existing in the prior art, the present invention provides a method for preparing an oxidation-resistant carbon aerogel composite material in a first aspect, the method comprising the following steps:

[0009] (1) synthesizing borosilicate modified phenolic resin by esterification reaction using a boron-containing modifier and a silicon-containing modifier;

[0010] (2) preparing borosilicate modified phenolic fiber by using the borosilicate modified phenolic resin under the protection of inert gas;

[0011] (3) preparing borosilicate modified phenolic fiber felt using the borosilicate modified phenolic fiber;

[0012] (4) impregnating the borosilicate modified phenolic fiber felt with the borosilicate modified phenolic resin and curing the felt to obtain a borosilicate modified phenolic fiber reinforced phenolic wet gel, and then drying the felt to obtain a borosilicate modified phenolic aerogel composite material;

[0013] (5) Carbonizing the borosilicate modified phenolic aerogel composite material to obtain a borosilicate modified carbon aerogel composite material.

[0014] The second aspect of the present invention provides a borosilicate modified carbon aerogel composite material prepared by the preparation method described in the first aspect of the present invention.

[0015] Compared with the prior art, the present invention has at least the following beneficial effects:

[0016] (1) By means of chemical modification, boron-silicon heteroatoms are introduced into phenolic resin, thereby obtaining a boron-silicon modified phenolic resin with high residual carbon. The boron-silicon modified phenolic resin is used as an organic precursor resin for preparing carbon aerogel, thereby achieving the anti-oxidation of the carbon aerogel matrix resin; at the same time, the boron-silicon modified phenolic resin is used to prepare phenolic fiber felt, thereby achieving the anti-oxidation of the reinforcement; the present invention synergistically improves the bulk anti-oxidation performance of the carbon aerogel composite material from two aspects: the matrix and reinforcement of the aerogel.

[0017] (2) Boron-silicon modified phenolic resin is used to prepare aerogel and reinforcement. The two have the same carbonization shrinkage rate and thermal weight loss law. During the carbonization process, the synergistic shrinkage of aerogel and reinforcement can be achieved, which solves the problem of interlayer cracking caused by the mismatch between the shrinkage of aerogel and reinforcement during the carbonization of organic aerogel composites, thereby obtaining a carbon aerogel composite material with significantly improved mechanical properties. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be fully described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] In a first aspect, the present invention provides a method for preparing an oxidation-resistant carbon aerogel composite material, the method comprising the following steps:

[0020] (1) synthesizing borosilicate modified phenolic resin by esterification reaction using a boron-containing modifier and a silicon-containing modifier;

[0021] (2) preparing borosilicate modified phenolic fiber by using the borosilicate modified phenolic resin under the protection of inert gas;

[0022] (3) preparing borosilicate modified phenolic fiber felt using the borosilicate modified phenolic fiber;

[0023] (4) impregnating the borosilicate modified phenolic fiber felt with the borosilicate modified phenolic resin and curing the felt to obtain a borosilicate modified phenolic fiber reinforced phenolic wet gel, and then drying the felt to obtain a borosilicate modified phenolic aerogel composite material;

[0024] (5) Carbonizing the borosilicate modified phenolic aerogel composite material to obtain a borosilicate modified carbon aerogel composite material.

[0025] The preferred embodiments of the present invention will be further described in steps below.

[0026] Step (1)

[0027] In this step, a boron-silicon-modified phenolic resin is synthesized by an esterification reaction using a boron-containing modifier and a silicon-containing modifier.

[0028] For example, the borosilicate-modified phenolic resin can be synthesized in the following manner: dissolving the phenolic resin in a first organic solvent, sequentially adding a boron-containing modifier and a silicon-containing modifier to carry out an esterification reaction, and obtaining the borosilicate-modified phenolic resin by removing the solvent.

[0029] In some preferred embodiments, the boron-containing modifier is any one of boric acid, phenylboric acid and p-hydroxyphenylboric acid.

[0030] In other preferred embodiments, the silicon-containing modifier is any one of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane and phenyltriethoxysilane.

[0031] In other preferred embodiments, the first organic solvent is any one of ethanol, ethylene glycol, n-propanol, isopropanol and n-pentanol.

[0032] In other preferred embodiments, the mass ratio of the phenolic resin, the silicon-containing modifier, the boron-containing modifier and the first organic solvent is (10, 20, 30 or 40):(1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12):(0.5, 1, 2, 3, 4, 5, 6, 7 or 8):100, for example, (10-40):(1-12):(0.5-8):100.

[0033] In other preferred embodiments, the esterification reaction is carried out under heating conditions, preferably the reaction temperature of the esterification reaction is 50°C to 120°C (50, 60, 70, 80, 90, 100, 110 or 120°C), and the reaction time is 5h to 20h (for example, 5, 10, 15 or 20h).

[0034] In other preferred embodiments, the solvent removal is carried out by vacuum distillation. More preferably, the distillation temperature of the vacuum distillation is 40°C to 150°C (40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140 or 150°C), the distillation pressure is 100Pa to 1000Pa (for example, 100, 200, 300, 400, 500, 600, 700, 800, 900 or 1000Pa), and the distillation time is 0.5h to 3h (0.5, 1, 2 or 3h).

[0035] Step (2)

[0036] In this step, the borosilicate modified phenolic resin is used to prepare borosilicate modified phenolic fiber under the protection of inert gas;

[0037] For example, the borosilicate modified phenolic fiber can be prepared in the following manner: placing the borosilicate modified phenolic resin obtained in step (1) in a spinning pot for heating and melting to obtain a borosilicate modified phenolic resin melt; applying pressure under the protection of an inert atmosphere such as argon to allow the borosilicate modified phenolic resin melt to be ejected through a spinning group to form borosilicate modified phenolic fiber precursors, and completing fiber precursor collection on a collection roller; immersing the borosilicate modified phenolic fiber precursors in a cross-linking and curing liquid for cross-linking and curing to obtain fiber filaments; washing and drying to obtain the borosilicate modified phenolic fiber;

[0038] In other preferred embodiments, the heating and melting temperature is 100° C. to 180° C. (eg, 100, 120, 140, 160 or 180° C.).

[0039] In other preferred embodiments, the applied pressure is 100 KPa to 300 KPa (eg, 100, 150, 200, 250 or 300 KPa).

[0040] In other preferred embodiments, the rotation speed of the wire collection roller is 300 rpm to 1500 rpm (for example, 300, 500, 1000 or 1500 rpm).

[0041] In some other preferred embodiments, the cross-linking curing liquid is a mixture of hydrochloric acid, hexamethylenetetramine and water. More preferably, the mass ratio of hydrochloric acid (1 mol / L), hexamethylenetetramine and water is (5-15): (5-20): (65-90), for example, (5, 10 or 15): (5, 10, 15 or 20): (65, 70, 75, 80, 85 or 90).

[0042] In other preferred embodiments, the immersion is carried out at room temperature, and the immersion time is 0.5 h to 3 h (eg, 0.5, 1, 2 or 3 h).

[0043] In other preferred embodiments, the curing temperature is 80°C to 160°C (for example, 90, 100, 110, 120, 130, 140, 150 or 160°C), and the curing time is 2h to 8h (2, 3, 4, 5, 6, 7 or 8h).

[0044] In other preferred embodiments, the washing is performed by repeatedly rinsing the fiber filaments with water until the pH value reaches 7.

[0045] In other preferred embodiments, the drying is to place the fiber filaments in a forced air drying oven and dry them at 60-80° C. (eg 60, 70 or 80° C.) for 6 h to 12 h (eg 6, 9 or 12 h).

[0046] Step (3)

[0047] In this step, the borosilicate modified phenolic fiber felt is prepared by using the borosilicate modified phenolic fiber;

[0048] For example, the borosilicate modified phenolic fiber felt can be prepared by: cyclically stacking and laying the borosilicate modified phenolic fiber obtained in step (2) in an XY plane to obtain a fiber web; needle-punching and stitching the fiber web in the Z direction to obtain the borosilicate modified phenolic fiber felt;

[0049] In other preferred embodiments, the stitching is performed using yarn obtained by spinning the borosilicate modified phenolic fiber obtained in step (2) of claim 1.

[0050] In other preferred embodiments, the paving is performed by selecting a paving angle at intervals of α from 0° along X and Y, and the value range of α is 30° to 45° (for example, 30, 33, 36, 39, 42 or 45°); preferably, the paving is performed starting from 0° along the XY plane in the angle sequence of “0°, 30°, 60°, 90°, -30°, -60°, -90°” or “0°, 45°, 90°, -45°, -90°”.

[0051] In other preferred embodiments, the volume content ratio of the yarn to the fiber felt is (0.01-0.1):1, for example, (0.01, 0.02, 0.03, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.10):1.

[0052] Step (4)

[0053] In this step, the borosilicate modified phenolic fiber felt is impregnated with the borosilicate modified phenolic resin and cured to obtain a borosilicate modified phenolic fiber reinforced phenolic wet gel, which is then dried to obtain a borosilicate modified phenolic aerogel composite material;

[0054] For example, the borosilicate modified phenolic aerogel composite material can be prepared in the following manner: the borosilicate modified phenolic fiber felt obtained in step (3) is placed in a mold, and is impregnated and cured with a phenolic resin solution to obtain a borosilicate modified phenolic fiber reinforced phenolic resin wet gel, and dried to obtain the borosilicate modified phenolic aerogel composite material, wherein the phenolic resin solution is prepared from the borosilicate modified phenolic resin obtained in step (1), a second organic solvent and a curing agent.

[0055] In other preferred embodiments, the second organic solvent is any one of ethanol, ethylene glycol, isopropanol, n-butanol and n-pentanol.

[0056] In other preferred embodiments, the curing agent is hexamethylenetetramine.

[0057] In other preferred embodiments, the mass ratio of the borosilicate modified phenolic resin, the curing agent, the second organic solvent and the borosilicate modified phenolic fiber felt is (5-20):(0.2-5):(20-200):1, for example, (5, 10, 15 or 20):(0.2, 0.4, 0.6, 0.8, 1, 2, 3, 4 or 5):(20, 50, 100, 150 or 200):1.

[0058] In other preferred embodiments, the impregnation is carried out as follows: maintaining the pressure for 5 min to 30 min (5, 10, 15, 20, 25 or 30 min) under a vacuum of 200 Pa to 5000 Pa (e.g., 200, 500, 1000, 2000, 3000, 4000 or 5000).

[0059] In other preferred embodiments, the curing temperature is 80°C to 160°C (80, 100, 120, 140 or 160°C), and the curing time is 12h to 36h (12, 18, 24, 30 or 36h).

[0060] The borosilicate modified phenolic aerogel is dried at normal pressure or supercritically, and preferably the drying is carried out at normal temperature and pressure.

[0061] Step (5)

[0062] In this step, the borosilicate modified phenolic aerogel composite material is carbonized to obtain a borosilicate modified carbon aerogel composite material.

[0063] For example, the borosilicate modified carbon aerogel composite material can be prepared in the following manner: the borosilicate modified phenolic aerogel composite material prepared in step (4) is carbonized in an inert atmosphere such as argon to obtain a borosilicate modified carbon aerogel composite material.

[0064] In other preferred embodiments, the carbonization temperature is 800° C. to 1400° C. (eg, 800, 1000, 1200 or 1400° C.), and the carbonization time is 0.5 h to 3 h (0.5, 1, 2 or 3 h).

[0065] The second aspect of the present invention provides a borosilicate modified carbon aerogel composite material prepared by the preparation method described in the first aspect of the present invention.

[0066] The borosilicate modified carbon aerogel composite material of the present invention has significantly improved anti-oxidation performance and can be used as a heat-insulating material in the field of high-temperature heat protection.

[0067] Example

[0068] The present invention is further described below in conjunction with the examples. The following examples cannot limit the scope of protection of the present invention, and any improvements made on the basis of the present invention that do not violate the spirit of the present invention are within the scope of protection of the present invention.

[0069] Example 1

[0070] (1) Add 10g of phenolic resin and 100g of anhydrous ethanol (as the first organic solvent) to a 1L three-necked flask, and stir to dissolve the phenolic resin. Add 0.5g of boric acid to the flask, and start stirring (stirring speed is 300rpm) and heating at the same time, and react at 50°C for 5h. Then add 1g of methyltrimethoxysilane to the flask, and continue to react for 5h under heating. After the product is cooled to room temperature, it is transferred to the rotary bottle of a rotary evaporator, and the solvent is removed by vacuum distillation (the distillation temperature of the vacuum distillation is 40°C, the distillation time is 0.5h, and the system pressure is 100Pa) to obtain borosilicate modified phenolic resin.

[0071] (2) Weigh 100g of borosilicate modified phenolic resin and place it in a spinning pot, heat it to 100°C, and melt-spin it at a spinning roller speed of 300rpm in an argon atmosphere and a pressure of 100KPa to obtain borosilicate modified phenolic raw silk fibers. The obtained raw silk fibers are placed in a cross-linking curing liquid with a mass ratio of hydrochloric acid (concentration of 1mol / L), hexamethylenetetramine (as a curing agent), and deionized water of 5:5:65, and pre-treated and soaked at room temperature for 0.5h, then heated to 80°C and kept warm for 2h, then the fibers are taken out and washed with water until neutral, and then transferred to a blast drying oven and dried at 70°C for 2h to obtain borosilicate modified phenolic fibers.

[0072] (3) The borosilicate modified phenolic fibers obtained in step (2) are cyclically stacked and laid at angles of "0°, 30°, 60°, 90°, -30°, -60°, -90" in the XY plane to obtain a phenolic fiber mesh, and then the yarn (linear density of 2K) obtained by spinning the borosilicate modified phenolic fibers obtained in step (2) is needle-punched and stitched in the Z direction so that the volume content ratio of the fibers in the XY plane and the Z direction is 1:0.01 (referred to as (x+y) / z direction ratio), thereby obtaining a borosilicate modified phenolic fiber felt.

[0073] (4) placing the borosilicate modified phenolic fiber felt obtained in step (3) into a mold; mixing the borosilicate modified phenolic resin (obtained in step (1)), hexamethylenetetramine, ethanol and borosilicate modified phenolic fiber felt in a mass ratio of 5:0.2:20:1 (raw material ratio) to obtain a resin solution; transferring the resin solution to the mold containing the borosilicate modified phenolic fiber felt obtained in step (3) under the condition that the vacuum degree in the mold is 200 Pa, maintaining the pressure for 5 minutes, exhausting the air bubbles, placing the solution in an oven, and curing at 80° C. for 12 hours to obtain a borosilicate modified phenolic fiber reinforced phenolic wet gel; and drying the solution at room temperature and pressure to a constant weight after demolding to obtain a borosilicate modified phenolic fiber reinforced phenolic aerogel composite material.

[0074] (5) The borosilicate modified phenolic fiber reinforced phenolic aerogel composite material was transferred to an atmosphere furnace and carbonized at 800°C for 0.5 h under an argon atmosphere to obtain a borosilicate modified carbon aerogel composite material.

[0075] (6) Material performance test: The borosilicate modified carbon aerogel composite material obtained in step (5) was subjected to an isothermal static calcination experiment at 1400°C for 0.5h in a muffle furnace (the appearance, size and weight before and after static calcination were recorded). After the material was isothermally static calcined at 1400°C for 0.5h, the appearance of the material was intact without cracks, the thickness direction shrank by 6%, and the residual weight was 40%. The borosilicate modified carbon aerogel composite material obtained in step (5) was subjected to an oxyacetylene assessment test at 1400°C (the assessment time was 1500s), and the linear ablation rate was 6.34×10 -4mm / s, mass ablation rate is 7.28×10 -4 g / s. The compressive strength of borosilicate modified carbon aerogel composite material is 105MPa.

[0076] Examples 2 to 6

[0077] Examples 2 to 6 were carried out in substantially the same manner as Example 1, with the differences being as shown in Tables 1 to 3.

[0078] Comparative Example 1

[0079] This comparative example is carried out in substantially the same manner as Example 1, except that a carbon fiber felt having the same volume density is used to replace the borosilicate-modified phenolic fiber felt in step (3).

[0080] Comparative Example 2

[0081] This comparative example is carried out in substantially the same manner as Example 1, except that needle-punched phenolic fiber felt of the same bulk density is used to replace the borosilicate-modified phenolic fiber felt in step (3).

[0082] Comparative Example 3

[0083] This comparative example was carried out in substantially the same manner as Example 1, except that the same volume of phenolic resin was used to replace the borosilicate-modified phenolic resin used in step (4).

[0084]

[0085]

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an oxidation-resistant carbon aerogel composite material, characterized in that: The method comprises the following steps: (1) synthesizing borosilicate modified phenolic resin by esterification reaction using a boron-containing modifier and a silicon-containing modifier; (2) preparing borosilicate modified phenolic fiber by using the borosilicate modified phenolic resin under the protection of inert gas; (3) preparing borosilicate modified phenolic fiber felt using the borosilicate modified phenolic fiber; (4) impregnating the borosilicate modified phenolic fiber felt with the borosilicate modified phenolic resin and curing the felt to obtain a borosilicate modified phenolic fiber reinforced phenolic wet gel, and then drying the felt to obtain a borosilicate modified phenolic aerogel composite material; (5) Carbonizing the borosilicate modified phenolic aerogel composite material to obtain a borosilicate modified carbon aerogel composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the borosilicate modified phenolic resin is synthesized by: dissolving the phenolic resin in a first organic solvent, sequentially adding a boron-containing modifier and a silicon-containing modifier to carry out an esterification reaction, and obtaining the borosilicate modified phenolic resin by removing the solvent; In step (2), the borosilicate modified phenolic fiber is prepared by: placing the borosilicate modified phenolic resin obtained in step (1) in a spinning pot for heating and melting to obtain a borosilicate modified phenolic resin melt; applying pressure under the protection of an inert atmosphere such as argon to allow the borosilicate modified phenolic resin melt to be ejected through a spinning group to form borosilicate modified phenolic fiber precursors, and completing the fiber precursor collection on a collection roller; immersing the borosilicate modified phenolic fiber precursors in a cross-linking and curing liquid for cross-linking and curing to obtain fiber filaments; washing and drying to obtain the borosilicate modified phenolic fiber; In step (3), the borosilicate modified phenolic fiber felt is prepared by: cyclically stacking and laying the borosilicate modified phenolic fiber obtained in step (2) in an XY plane to obtain a fiber web; and needle-punching and stitching the fiber web in the Z direction to obtain the borosilicate modified phenolic fiber felt. In step (4), the borosilicate modified phenolic aerogel composite material is prepared by the following method: the borosilicate modified phenolic fiber felt obtained in step (3) is placed in a mold, and impregnated and cured with a phenolic resin solution to obtain a borosilicate modified phenolic fiber reinforced phenolic wet gel, and dried to obtain the borosilicate modified phenolic aerogel composite material, wherein the phenolic resin solution is prepared by the borosilicate modified phenolic resin obtained in step (1), a second organic solvent and a curing agent; and / or In step (5), the borosilicate modified carbon aerogel composite material is prepared by carbonizing the borosilicate modified phenolic aerogel composite material prepared in step (4) in an inert atmosphere such as argon to obtain a borosilicate modified carbon aerogel composite material.

3. The preparation method according to claim 2, characterized in that: In step (1): The boron-containing modifier is any one of boric acid, phenylboric acid and p-hydroxyphenylboric acid; The silicon-containing modifier is any one of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane and phenyltriethoxysilane; and / or The first organic solvent is any one of ethanol, ethylene glycol, n-propanol, isopropanol and n-pentanol.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1): The mass ratio of the phenolic resin, the silicon-containing modifier, the boron-containing modifier and the first organic solvent is (10-40):(1-12):(0.5-8):

100.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (1): The esterification reaction is carried out under heating conditions, and preferably the reaction temperature of the esterification reaction is 50° C. to 120° C., and the reaction time is 5 h to 20 h.

6. The preparation method according to any one of claims 2 to 5, characterized in that In step (2): The cross-linking curing liquid is a mixture of hydrochloric acid, hexamethylenetetramine and water. Preferably, the mass ratio of the hydrochloric acid, hexamethylenetetramine and water is (5-15): (5-20): (65-90).

7. The preparation method according to any one of claims 2 to 6, characterized in that In step (3): The stitching is performed by spinning the borosilicate-modified phenolic fiber obtained in step (2) of claim 1 to obtain the yarn; Preferably, the volume content ratio of the yarn to the fiber felt is (0.01-0.1):

1.

8. The preparation method according to any one of claims 2 to 7, characterized in that: In step (4): The second organic solvent is any one of ethanol, ethylene glycol, isopropanol, n-butanol and n-pentanol; and / or the curing agent is hexamethylenetetramine; Preferably, the mass ratio of the borosilicate modified phenolic resin, the curing agent, the second organic solvent and the borosilicate modified phenolic fiber felt is (5-20):(0.2-5):(20-200):

1.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (5): The carbonization temperature is 800° C. to 1400° C., and the carbonization time is 0.5 h to 3 h.

10. A borosilicate modified carbon aerogel composite material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Group modified phenolic resin and method for preparing high-strength phenolic fiber

    CN117624515A

  • A group-modified phenol-aldehyde resin and a method for producing a high-strength phenol-aldehyde fiber

    CN117624515B

  • Antioxidant modified carbon fiber-carbon aerogel composite material and preparation method thereof

    CN121779138A